An Inquiry into Inferior and Superior Role Portrayals in Multi-racial Television Advertisements - De la Rey Van der Waldt (Communicare)
This study is an analysis of black and white respondents' reactions to inferior and superior role portrayals In South African multi-racial television advertisements. The study was contracted with 116 white students from the UOFS and 116 black students from the UFH. General results of similar type of studies in the United States indicated a somewhat stereotyped and partly inferior role portrayal of blacks in advertising.